The relationship between preoperative serum immunoglobulin levels and the development of bacteremia after tonsillectomy - Keleş, Erol; Gök, Üzeyir; Alpay, Hayrettin Cengiz; Aral, Murat (İstanbul Üniversitesi, 2004)
Objectives: We examined the risk tor the develop ment of bacteremia during tonsillectomy and evaluated the presence of an association between bacteremia and preoperative serum immunoglobulin levels.Patients and Methods: The study included 40 patients 16 males, 24 females; mean age 16.8 years; range 5 to 35 years who undervvent tonsillectomy with the useofthedissection-sneartechnique. Preoperatively, venous blood samples were collected from ali the patients to determine serum immunoglobulin levels and the presence or absence of bacteremia. Bacteremia was also investigated in blood samples postoperatively.Results: There was no growth in the preoperative blood cultures, but bacteremia was documented in 10 patients 25% after tonsillectomy. Increased serum IgG levels were determined in 15 patients before operation, seven of whom developed bac teremia after tonsillectomy p0.05 .Conclusion: Although our current knowledge does not allow to predict bacteremia following tonsillectomy in advance, the finding that seven of 10 patients who devel oped bacteremia had increased preoperative IgG levels draws attention to serum IgG, especially in patents in whom bacteremia may present additional risks.

Amaç: Tonsillektomi sırasında bakteriyemi gelişimriskini gözden geçirmek ve bakteriyemi ile ameliyatöncesi serum immünglobülin düzeylerinin olası bağlantısını değerlendirmek.Hastalar ve Yöntemler: Çalışmaya tonsillektomi endikasyonu konan ve snear diseksiyon tekniği yoluylatonsillektomi uygulanan 40 hasta 16 erkek, 24 kadın;ort. yaş 16.8; dağılım 5-35 years alındı. Tüm hastalardan ameliyat öncesinde alınan venöz kan örneklerinde serum immünglobülin düzeyleri araştırıldı ve kültürsonuçları değerlendirildi. Ameliyat sonrası alınan örneklerde bakteriyemi varlığı araştırıldı.Bulgular: Ameliyat öncesindeki kan kültürlerinin hiçbirinde üreme olmamasına karşın, tonsillektomi sonrasında kan örneklerinin %25’inde bakteriyemi saptandı.Serum IgG düzeyinin ameliyat öncesinde 15 hastadayüksek olduğu belirlendi; bu hastaların yedisinde tonsillektomi sonrasında bakteriyemi gelişti p0.05 .Sonuç: Bugünkü bilgilerimize göre, tonsillektomi ameliyatı sonrasında gelişen bakteriyemiyi ameliyat öncesinde belirlemek mümkün olmasa da, bakteriyemi gelişen10 hastanın yedisinde serum IgG düzeyinin yüksek bulunması, özellikle bakteriyeminin ek risk oluşturacağıhastalarda dikkati IgG’ye çekmektedir
Ameliyat öncesindeki serum immünglobülin düzeyleri ile tonsillektomi sonrasında bakteriyemi gelişmesi arasındaki ilişki